A Semiotic Study of Angkot Signage in Ambon: Decoding Public Messaging on Wheels - Matatula, Marles Yohannis; Tupalessy, Pricilia; Patty, Jusak (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
This study explores stickers' semiotic and cultural significance on public minibusses (angkot) in Ambon City, Indonesia, through a multimodal analysis grounded in Roland Barthes' (1964) denotative and connotative meaning framework. The research examines five angkot stickers and investigates how these mobile, grassroots texts encode literal and symbolic messages, reflecting Ambon's sociocultural values, linguistic hybridity, and glocalized identities. The findings reveal that the stickers combine informal and formal Bahasa Indonesia, colloquial Ambonese Malay, and global pop culture references to convey themes of faith, resilience, humor, and social critique. Their placement on angkot transforms these vehicles into mobile billboards, circulating localized messages across urban spaces and challenging traditional notions of static linguistic landscapes. This study addresses gaps in linguistic landscape research by focusing on transient, user-generated signage, highlighting the agency of drivers and local artists in shaping public discourse. It underscores the importance of grassroots creativity in mediating cultural identity. It offers insights into how ephemeral texts contribute to the dynamic interplay of global and local influences in post-colonial urban environments.